Circulating Progenitor Cells Identify Peripheral Arterial Disease in Patients With Coronary Artery Disease. Issue 4 (5th August 2016) - Hayek, Salim S.; MacNamara, James; Tahhan, Ayman S.; Awad, Mosaab; Yadalam, Adithya; Ko, Yi-An; Healy, Sean; Hesaroieh, Iraj; Ahmed, Hina; Gray, Brandon; Sher, Salman S.; Ghasemzadeh, Nima; et al.
Abstract : Rationale: : Peripheral arterial disease (PAD) is a clinical manifestation of extracoronary atherosclerosis. Despite sharing the same risk factors, only 20% to 30% of patients with coronary artery disease (CAD) develop PAD. Decline in the number of bone marrow–derived circulating progenitor cells (PCs) is thought to contribute to the pathogenesis of atherosclerosis. Whether specific changes in PCs differentiate patients with both PAD and CAD from those with CAD alone is unknown. Objective: : Determine whether differences exist in PCs counts of CAD patients with and without known PAD. Methods and Results: : 1497 patients (mean age: 65 years; 62% men) with known CAD were identified in the Emory Cardiovascular Biobank. Presence of PAD (n=308) was determined by history, review of medical records, or imaging and was classified as carotid (53%), lower extremity (41%), upper extremity (3%), and aortic disease (33%). Circulating PCs were enumerated by flow cytometry. Patients with CAD and PAD had significantly lower PC counts compared with those with only CAD. In multivariable analysis, a 50% decrease in cluster of differentiation 34 (CD34+) or CD34+/vascular endothelial growth factor receptor-2 (VEGFR2+) counts was associated with a 31% ( P =0.032) and 183% ( P =0.002) increase in the odds of having PAD, respectively. CD34+ and CD34+/VEGFR2+ counts significantly improved risk prediction metrics for prevalent PAD. Low CD34+/VEGFR2+ counts were associated with a 1.40-fold (95% confidence interval, 1.03–1.91) and a 1.64-fold (95% confidence interval, 1.07–2.50) increases in the risk of mortality and PAD-related events, respectively. Conclusions: : PAD is associated with low CD34+ and CD34+/VEGFR2+ PC counts. Whether low PC counts are useful in screening for PAD needs to be investigated. Abstract : Supplemental Digital Content is available in the text.